The ceramic art of James Tower - Wilcox, Timothy; Tower, James 1919-1988. (Farnham, United Kingdom Lund Humphries, 2012)
James Tower (1919-88) is widely regarded as one of the most distinctive figures in post-war British ceramics. This book provides a comprehensive visual document of Tower's work, incorporating a complete illustrated catalogue. It also includes a detailed biography, setting Tower in the social and artistic context in which he lived and worked.
Keywords: Pottery, British -- 20th century -- Biography